2019
DOI: 10.1111/rssb.12313
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Inference for the Population Landscape via Moment-Adjusted Stochastic Gradients

Abstract: Summary Modern statistical inference tasks often require iterative optimization methods to compute the solution. Convergence analysis from an optimization viewpoint informs us only how well the solution is approximated numerically but overlooks the sampling nature of the data. In contrast, recognizing the randomness in the data, statisticians are keen to provide uncertainty quantification, or confidence, for the solution obtained by using iterative optimization methods. The paper makes progress along this dire… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In addition, Fang et al [2018], Fang [2019] proposed online bootstrap procedures for the estimation of confidence intervals via randomly perturbed SGD. Meanwhile, , Su and Zhu [2018], Liang and Su [2019] proposed variants of the SGD algorithm to facilitate inference in a non-asymptotic fashion.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, Fang et al [2018], Fang [2019] proposed online bootstrap procedures for the estimation of confidence intervals via randomly perturbed SGD. Meanwhile, , Su and Zhu [2018], Liang and Su [2019] proposed variants of the SGD algorithm to facilitate inference in a non-asymptotic fashion.…”
Section: Related Workmentioning
confidence: 99%
“…Kingma and Ba (2015) introduced Adam, computing adaptive learning rates for different parameters from estimates of first and second moments of the gradients. Liang and Su (2019) employed a similar idea as AdaGrad to adjust the gradient direction and showed that the distribution for inference can be simulated iteratively. Toulis and Airoldi (2017) developed implicit SGD procedures and established the resulting estimator's asymptotic normality.…”
Section: Introductionmentioning
confidence: 99%
“…Fang et al (2018) and Fang (2019) proposed bootstrap procedures for constructing confidence intervals through perturbed-SGD. Meanwhile, variants of SGD algorithm and corresponding inference in non-asymptotic fashion are studied in Su and Zhu (2018) and Liang and Su (2019).…”
Section: Introductionmentioning
confidence: 99%